SCHEDULING OPTIMISATION UNDER CONTRADICTIONS IN CRITERIA FUNCTIONS - Okhremchuk, Olena Sergeevna (Science-based technologies, 2019)
The article deals with the analysis of methods for constructing a production schedule based on the theory of planning. It is shown that the most effective step in this process is to optimise the airline's activity at all levels - economic, technical, informational, and others. As optimisation of scheduling is of crucial importance in the process of organizing effective airline operations, the possibilities of using this theory in creating optimal graphics for medium and large organizations are considered. The problem of optimisation of planning in a one-stage system with a single drive and a set of N services is considered. Selected and comparatively the most appropriate approaches to effective construction of optimal schedule. In order to streamline the criteria for optimality of the schedule to ensure the convenience of description, storage and program implementation, the conditional division of criteria into categories is proposed. Each of the geographical, technical or transit criteria is mathematically described by the corresponding value of the priority. The paper proposes a method of prioritising criteria for different categories. The method is based on the theoretical basis for the of the Saati analytics hierarchy process, modified for this specific problem. From the mathematical and logical point of view, this will mean weight changes, or the content of certain criteria, changes in the values ​​of their priorities, but in principle, the proposed approach to enterprise planning will remain unchanged. The presented demonstrates the versatility of the proposed approach to scheduling and its ability to meet the requirements of carriers of fundamentally different scales. The paper gives recommendations on the construction of appropriate software schemes for an automated planning system. Firstly, its flexibility with regard to possible future reprogramming for its new needs, criteria and priorities must be envisaged, and secondly, its structure should have a modular architecture to ensure the convenience of making changes to individual parts without disrupting the rest of the system.